Pengaruh Pengetahuan Perpajakan, Kesadaran Wajib Pajak, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Daerah dalam Membayar Pajak Restoran - Prasetyo Pambudi; Yanuar Eko Restianto; Widyahayu Warmmeswara Kusumastati (Jurnal Riset Akuntansi Soedirman, 2026)
This research tested the influences of taxation knowledge, tax payer awareness and tax penalty to local tax payer obedience in paying restaurant tax. This research used 112 restaurant sample in Cilacap’s District. It used questionarre as data collection tool. Research method used was multiple linear regression, which was done after doing validation test, reliability test, and classical assumption tests. The result showed that taxation knowledge and tax payer awareness influence significantly local tax payer obedience in paying restaurant tax. While tax penalty did not influence significantly local tax payer obedience in paying restaurant tax.